Journeys of the Apostle Paul: follow the life & ministry of Christianity's leading missionary - Keener, Craig S. (Lexham Press, 2019)
"Follow the Life and Ministry of Christianity's Leading Missionary. The Apostle Paul is one of the most important figures in the early church. He is a main character in the narrative woven through the book of Acts and his thirteen letters make up a significant portion of the New Testament canon. Because Acts and his letters appear as discrete books in Scripture, it can be difficult to piece together a clear narrative for Paul's life and ministry. In Journeys of the Apostle Paul, 20 contributors present a coherent picture of Paul's life, connecting the events in Acts to his letters and theological teaching. With beautifully rendered maps and timelines, this book takes readers through the Acts narratives of Paul's journeys step by step-his interrupted journey to Damascus while persecuting Christians; his three missionary journeys; and his long journey from Jerusalem to Rome. Along the way, you'll discover new insights into his life, his teaching, and his role in the early church"--